Analyzing the Dispersion Properties and Bearing Capacity of Clays by Geotechnical Investigation: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With this study, Bottom Ash (BA) and EcoSand (ES) which are actually construed as a waste product from the cement sector are actually tried as alternative materials for steadying clay. On realizing the significance of environmental protection against the unscrupulous dumping of waste materials of all of the types, it's turned out to be the demand of the hour to check out the feasibilities of exploiting them in an advantageous manner. This particular study has found that the waste by-products ES and BA have the potential to enhance the attributes of clay.